2022
DOI: 10.3390/healthcare10081515
|View full text |Cite
|
Sign up to set email alerts
|

Application of Honey to Reduce Perineal Laceration Pain during the Postpartum Period: A Randomized Controlled Trial

Abstract: Perineal lacerations affect between 35 and 85% of women during childbirth and may be responsible for postpartum pain. Honey has been demonstrated to have interesting properties that can promote wound healing. The aim was to evaluate the effectiveness of the application of honey to the perineum to reduce perineal pain during the early postpartum period. A randomized controlled trial including 68 women was conducted. In the intervention group, honey was applied to perineal lacerations for four days, in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…As detailed in Figure 1 , our comprehensive search yielded 1453 results, of which 421 were duplicate records, and 1019 articles were deemed unrelated based on title or abstract review and were excluded. The remaining seven articles were carefully selected and, after evaluating inclusion and exclusion criteria, 5 RCTs [ 1 , 14 , 17 , 18 , 19 ] were included in this systematic review and meta-analysis. The reasons for exclusion of studies were: overlapping studies ( n = 5) and others ( n = 2), comprising a study published in another language and a study with measurements (mean/standard deviation) different from those used in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As detailed in Figure 1 , our comprehensive search yielded 1453 results, of which 421 were duplicate records, and 1019 articles were deemed unrelated based on title or abstract review and were excluded. The remaining seven articles were carefully selected and, after evaluating inclusion and exclusion criteria, 5 RCTs [ 1 , 14 , 17 , 18 , 19 ] were included in this systematic review and meta-analysis. The reasons for exclusion of studies were: overlapping studies ( n = 5) and others ( n = 2), comprising a study published in another language and a study with measurements (mean/standard deviation) different from those used in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The moment of childbirth, whether normal or through a surgical procedure, can lead to complications. This highlights the need for effective treatments and proper wound management using cost-effective methods that promote maternal well-being, reduce mortality, improve healing, and control pain [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A randomized controlled trial examined the use of medicinal honey on perineal wounds postpartum and found that there was no significant difference in the intensity or perception of pain between the two groups [16 ▪ ]. However, despite finding no difference in pain, 93% of women in the intervention group reported being satisfied with the use of honey on their perineum.…”
Section: Local Wound Care and Topical Agentsmentioning
confidence: 99%